The development and validation of a reverse transcription recombinase polymerase amplification assay for detection of flaviviruses - Bonnet, Elisabeth Hendrika (University of the Free State, 2019)
Flaviviruses have been of clinical importance since ancient times. Five flaviviruses are known to occur or have been identified historically in South Africa (SA) namely, West Nile virus (WNV), Usutu virus (USUV), Wesselsbron virus (WSLV), Spondweni virus (SPOV) and Banzi virus (BANV). Medically significant flaviviruses, WNV and WSLV, are known to occur annually in SA. Development of isothermal assays, such as recombinase polymerase amplification (RPA), plays an important role in performing surveillance studies and increasing diagnostic capacity for emerging viral pathogens in limited resource settings. In their native form, WNV and WSLV can only be handled in a biosafety laboratory level 3 and this restricts laboratories that lack such resources, hence transcribed RNA controls were successfully prepared for WNV, USUV and WSLV to develop and validate a RT-RPA for the detection of flaviviruses. A lateral-flow RT-RPA was developed by identifying theoretical cross reactivity between the probe and primer candidates by sequence alignments of the conserved NS5 protein of WNV, USUV and WSLV. It was determined that a few mismatches were present between WNV and USUV in the probe binding region and in the reverse primer, as well as between WNV and WSLV, hence different probe and reverse primer regions were identified for WNV/USUV and WSLV. A limitation of the study was the selection of a reference strain of WNV belonging to lineage 1 as a lineage 2 isolate would have been a more suitable representative of SA lineages. Nonetheless, RNA from SA isolate 93/01 was amplified using the RT-RPA. The sensitivity of the assay was determined by diluting RNA control ten-fold, and was found that the WNV RT-RPA could detect WNV and USUV transcribed RNA diluted 109 fold, whereas the WSLV RT-RPA detected WSLV transcribed RNA diluted 1010 fold. Testing RNA from other arboviruses suggested that despite the binding tolerability of the assay there was good specificity as no other arboviruses were amplified. However because of similarity in sequence data, USUV transcribed RNA was detected with the WNV RT-RPA and WSLV RT-RPA. Theoretical cross reactivities with other flaviviruses were determined by sequence alignments of the NS5 region and it was proposed that Japanse encephalitis virus (JEV), Zika virus (ZIKV) and dengue virus (DENV) RNA will not be detected by either the WNV RT-RPA or WSLV RT-RPA. Seventeen pools of Culex spp mosquitoes were screened for flavivirus RNA, although no flaviviruses were expected within such a small cohort. Lack of amplification inhibitors in the mosquito samples was confirmed by spiking known negative mosquito samples with transcribed flavivirus RNA and performing a RT-RPA using the spiked samples. Detecting WNV by RT-RPA will not only be useful for surveillance studies in SA, but can also be used as a diagnostic tool for veterinary diagnostics, especially equine. In conclusion, the development and validation of a RT-RPA for the detection of WNV, WSLV and USUV flaviviruses was successful. The RT-RPA proved to be a robust, rapid and sensitive assay that might have potential as a diagnostic tool in the field or resource limited settings.
Dissertation (M.Med.Sc. (Virology))--University of the Free State, 2019
Keywords: Flaviviruses; West Nile virus; Usutu virus; Wesselsbron virus; Limited resource settings; Transcribed RNA; RT-RPA; Sensitive; Robust; Rapid; Isothermal